Influence of Family and Childhood Memories in the Development and Manifestation of Paranoid Ideation - Carvalho, Célia Barreto (2016)
Several studies point out to the influence of social experiences on perceptions of the environment and others in cognitive functioning and different aspects of psychopathology. The current study aimed at studying the influence of the psychosocial risk factors in a mixed sample of participants from the general population and affected by paranoid schizophrenia. The extent to which the existence of negative life events and events that are threatening to the inner models of the self (i.e., history of maltreatment, physical, social or psychological abuse) or the memories of these traumatic events occurring during childhood are related to the existence of paranoid beliefs in adulthood was explored. Results suggested that memories of parental behaviours characterized by antipathy from both parental figures, submissiveness and bullying victimization were important predictors of paranoid ideation in adult life. This further emphasizes the need for understanding the family and social dynamics of people presenting paranoid ideations to the development of therapeutic interventions that can effectively reduce the invalidation caused by severe psychopathology, as is the case of schizophrenia. Copyright © 2015 John Wiley & Sons, Ltd.